2007
DOI: 10.1111/j.1600-0528.2007.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators for recurrent aphthous ulcers among adults in the US

Abstract: This study establishes the prevalence of RAU among adults in the US and demonstrates that whereas cigarette smoking is associated with lesser odds, low insulin levels might be independently associated with greater odds of RAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 30 publications
7
47
1
6
Order By: Relevance
“…The hypotheses of its pathogenesis are numerous. Several studies have reported a relationship between RAS and various causes but the results are conflicting (Scully 2006;Chattopadhyay and Chatterjee 2007). Different subgroups of patients appear to have different causes for the occurrence of RAS.…”
Section: © 2008 Tohoku University Medical Pressmentioning
confidence: 99%
“…The hypotheses of its pathogenesis are numerous. Several studies have reported a relationship between RAS and various causes but the results are conflicting (Scully 2006;Chattopadhyay and Chatterjee 2007). Different subgroups of patients appear to have different causes for the occurrence of RAS.…”
Section: © 2008 Tohoku University Medical Pressmentioning
confidence: 99%
“…It is clinically diagnosed by painful, recurrent, yellowish white or grey, single or multiple, and round or oval ulcers with erythematous margins mainly confined to non-keratinized oral mucosa. 7,18,23,24 Its pathogenesis remains uncertain but is probably multifactorial. 7,18,23,24 The need for consideration of psychological factors in the pathogenesis of oral disease has been increasingly acknowledged over the last decades and many studies have highlighted the psycho-social impact of oral conditions.…”
mentioning
confidence: 99%
“…7,18,23,24 Its pathogenesis remains uncertain but is probably multifactorial. 7,18,23,24 The need for consideration of psychological factors in the pathogenesis of oral disease has been increasingly acknowledged over the last decades and many studies have highlighted the psycho-social impact of oral conditions. Oral health and status impacts on people's daily living, quality of life and overall well-being, therefore, the clinical status, psychological factors, dental needs and patients' perceptions should be assessed.…”
mentioning
confidence: 99%
“…1 Family history is the most consistent factor associated with RAS. 2 Additional factors associated with the disease include nutritional deficiencies, stress, and systemic diseases.…”
Section: Discussionmentioning
confidence: 96%